Synthesis, characterization and determination of the metal ions adsorption capacity of cellulose modified with p-aminobenzoic groups - Castro, Gustavo Rocha De [UNESP]; Alcântara, Ilton Luiz De [UNESP]; Roldan, Paulo Dos Santos [UNESP]; Bozano, Dorotéia De Fátima [UNESP]; Padilha, Pedro De Magalhães [UNESP]; Florentino, Ariovaldo De Oliveira [UNESP]; Rocha, Julio Cesar [UNESP] (ABM, ABC, ABPol, 2004)
This paper describes the synthesis and characterization of p-aminobenzoic modified cellulose (Cell-PAB), as well as the separation and preconcentration of Cd(II), Cu(II), Ni(II), Pb(II) and Zn(II) ions from an aqueous medium using a Cell-PAB bath and the column technique. The quantity of p-aminobenzoic groups attached to the cellulose surface, i.e., 1.81±0.04 mmol/g, was determined by elemental analysis. The FT-IR spectra of Cell-PAB revealed characteristic bands of p-aminobenzoic groups, indicating the desired functionalization of the cellulose surface. The adsorptive capacities for the metals (Ns) Cd, Cu, Ni, Pb and Zn (Ns) were, respectively, 1.72 ± 0.02, 1.96 ± 0.02, 1.88 ± 0.04, 2.01 ± 0.03 and 1.93 ± 0.03 mmol/g. Metal separations performed in flow experiments using a column packed with 1 g of Cell-PAB and 5 mL of 1.5 mol/L HCl solution as eluent achieved an almost 100% metal ions recovery rate.
Keywords: modified cellulose; separation of heavy metals; preconcentration; adsorption; p-aminobenzoic groups